2018
DOI: 10.1038/s41598-018-19286-1
|View full text |Cite
|
Sign up to set email alerts
|

The suppressive role of calcium sensing receptor in endometrial cancer

Abstract: Studies have shown that calcium sensing receptor (CaSR) is involved in the progressions of several human cancers. However, the role of CaSR in endometrial cancer remains unknown. This study provides a preliminary analysis of the CaSR effect on endometrial cancer development. Ectopic CaSR expression by lentiviral transfection (CaSR-OV) in Ishikawa cells significantly increased intracellular calcium ([Ca2+]i) levels and cell apoptosis. E-cadherin and β-catenin expression and complex formation at the membrane wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…CASR encodes a calcium-sensing receptor, which is a plasma membrane G protein-coupled receptor involved in calcium homeostasis (48). In human endometrium, CASR was reported to play an inhibitory role in endometrial cancer (49). CASR protein is only expressed in epithelial cells, which mediates the secretion of stanniocalcin-1, a glycoprotein significantly up-regulated in midsecretory endometrial fluid of fertile endometrium (50).…”
Section: Discussionmentioning
confidence: 99%
“…CASR encodes a calcium-sensing receptor, which is a plasma membrane G protein-coupled receptor involved in calcium homeostasis (48). In human endometrium, CASR was reported to play an inhibitory role in endometrial cancer (49). CASR protein is only expressed in epithelial cells, which mediates the secretion of stanniocalcin-1, a glycoprotein significantly up-regulated in midsecretory endometrial fluid of fertile endometrium (50).…”
Section: Discussionmentioning
confidence: 99%
“…VEGFR3 has also been shown to be expressed in neuronal progenitors, osteoblasts, and macrophages [50,51,52]. Furthermore, recent studies have indicated that VEGFR3 expression is detected in different types of cancers and it contributes to tumor progression and lymphatic metastasis (Table 1) [53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93].…”
Section: Regulation Of Vegfr3 Signalingmentioning
confidence: 99%
“…Immunohistochemical analysis and qRT-PCR studies have demonstrated that the expression of VEGFR3 was increased in endometrial carcinomas compared with normal endometrium [64,65]. Additionally, VEGFR3 expression was significantly associated with tumor stage and poor disease-free survival in endometrial carcinomas [64].…”
Section: Clinical Significance Of Vegf-c/vegfr3 Expression In Tumorsmentioning
confidence: 99%
“…Consistently, in a clinical study with large sample sizes and long follow-up periods, Yang et al (2018) found that CaSR-positive expression status was essential for the antineoplastic effect of calcium in colorectal cancer (Yang et al, 2018). Our previous work showed that CaSR activation reduced cell viability and induced apoptosis in endometrial cancer (Xin et al, 2018). These discrepancies of the roles of CaSR on tumor progression among different types of cancers imply that it might be tissue or disease specific.…”
Section: Introductionmentioning
confidence: 70%